Study of Computational Biotechnology (Bioinformatics) on Telang Flower Kombucha (Clitoria Terantea L) as an Immunomodulator to Suppress Immunoglobulin E (IgE) for Allergy Sufferers - Nurrizka Kurniawati; Ika Sutra Permirahayu Aji Saputri; Firman Rezaldi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Telang flower kombucha has been known to have pharmacological movement in vitro in repressing the development of microbes and organisms. Besides that, it also has the potential in vivo to inhibit cholesterol in livestock, so that it can be used or utilized as an active ingredient in drugs and cosmetics. In addition, allergy can cause immunity to tend to decrease due to the synthesis of immunoglobulin E protein, so this study aims to provide an initial picture for allergy sufferers through computational biotechnology or bioinformatics studies on the vitexin compound in tela flower kombucha to inhibit the formation of IgE as a cause of allergy based on its binding affinity value. The research method used was molecular docking and validation of the vitexin compound in butterfly pea flower kombucha in inhibiting IgE formation. The results of single point calculations and geometric optimization of the vitexin compound in butterfly pea flower kombucha were 2.99585 kcal/mol and 5.20442 kcal/mol respectively. The research results show that based on the binding affinity value of -7.1, vitexin contained in telang flower kombucha is able to inhibit the formation of Immunoglobulin E (IgE) as one of the causes of allergies.